Restore hearing naturally : how to use your inner resources to bring back full hearing - Stucki, Anton (Rochester, Vermont : Healing Arts Press, 2020)
"A step-by-step training program to improve your hearing through enhanced perception with all five senses"--
"Originally published in German under the title Besser horen leichter leben by AT Verlag"--Title page verso.
Includes bibliographical references (pages 259-263) and index.
108916
Keywords: Hearing disorders -- Treatment; Self-help publications; Handbooks and manuals